Analysis of Factors Associated with Blood Glucose Levels among Type 2 Diabetes Mellitus Patients at Jatinegara Public Health Center in 2025 - Cucu Wayamah; Yenny Sulistyowati; Santi Agustina; Diah Hayati; Siti Sutilah (CV. Inara, 2025)
Background: Type 2 diabetes mellitus (T2DM) is one of the most prevalent non-communicable diseases in Indonesia. Blood glucose control is essential to prevent complications; therefore, identifying associated factors is crucial. Objective: To determine the factors associated with random blood glucose (RBG) levels among T2DM patients enrolled in the Prolanis program at Jatinegara Health Center in 2025. Methods: This study employed an analytical cross-sectional design involving 92 T2DM Prolanis patients. Data were collected through interviews, questionnaires, anthropometric measurements, and medical records. Data analysis included univariate, bivariate (chi-square), and multivariate (logistic regression). Results: Most respondents had normal RBG levels (80.4%), were female (76.1%), aged >60 years (56.5%), and had a family history of diabetes (57.6%). Non-modifiable factors (sex, age, family history) and modifiable factors (BMI, knowledge, stress, fiber intake, and physical activity) were not significantly associated with RBG levels (p>0.05). However, carbohydrate consumption patterns emerged as the dominant factor increasing the risk of hyperglycemia (OR=4.08; 95% CI=0.869–19.171). Conclusion: Carbohydrate consumption pattern was identified as the dominant factor associated with random blood glucose levels among T2DM Prolanis patients at Jatinegara Health Center. Nutritional interventions and education on low-glycemic index diets should be strengthened to improve glycemic control.